Measuring Setup for Investigation and Visualization of the Percolation Phenomenon in Non-Оrdered Models of Metal-Dielectric Nanocomposites - P. Okal (Приборы и методы измерений)
The study uses the phenomenon of high voltage partial discharge to investigate the phenomenon of percolation and visualisation of the percolation channel. The phenomenon of partial discharges is very similar to the quantum tunneling phenomenon observed in metal-dielectric nanocomposites. In both cases the flow of alternating current occurs in the absence of direct contact between the metallic phase particles.A measuring stand was developed and constructed to test models of metal dielectric nanocomposites using high voltage partial discharge. The stand consists of a 110 kV high voltage transformer, a voltage regulator protecting the constant rate of high voltage rise, a measuring system consisting of a measuring probe, voltmeters and a computer. The communication between the measuring probe and the voltmeter was made in digital technology with the use of fiber optic technology, which allowed the meter to communicate with the computer without any errors and eliminated the interference caused by a strong electromagnetic field resulting from the use of high voltage.Systems modelling metal-dielectric composites were built, consisting of metallic elements in the form of disks, randomly distributed on the surface of the dielectric matrix. The number of disks was increased in series of 40 in each. The maximum number of disks was 1520. The dependence was determined of one of the important parameters characterising an partial discharge, i. e. the initial voltage, at which an electric current starts to flow between electrodes, on the concentration of the metallic phase. On the basis of these results, a percolation threshold was established for a matrix with a random distribution of metallic phase elements, the value of which is about 50 %. Films and pictures of partial discharges with visible percolation channels were taken with the camera with which the stand was equipped.